Tranquil City: identifying opportunities for urban tranquillity to promote healthy lifestyles. Issue 1 (4th May 2021) - Waters, Grant; Warren, Ben; Ratcliffe, Eleanor; Godefroy, Julie
ABSTRACT: Rest and recuperation are fundamental to well-being. Experiencing tranquil spaces can support this need amid stressful urban living. Tranquil Pavement London helps people discover and share tranquil spaces and navigate via low pollution pathways, exploring connections between subjective and objective datasets. This paper discusses our approach, tools and ways forward.